Effect of High Jugular Bulb on the Hearing Loss Characteristics in Patients With LVAS: A Pilot Study - Kwesi, Arthur Benjamin; Yu, Jintao; Wang, Chenlu; Wang, Yonghua; Chuang, Fengyi; Yan, Xiaohui; Shi, Wendi; Sun, Yu (Frontiers in Cell and Developmental Biology, 2021)
Objective: Both large vestibular aqueduct syndrome (LVAS) and high jugular bulb (HJB) are regarded as abnormalities commonly seen on the temporal bone CT. High jugular bulb has been found to erode the vestibular aqueduct, and there are several studies on jugular bulb vestibular aqueduct dehiscence. But there is no study that specifically reports LVAS with concurrent HJB, and its hearing loss relatedness. This study presents the pure tone audiometry differences between LVAS with HJB, and LVAS without HJB. Methods: A case control study involving 36 bilateral LVAS with concurrent unilateral HJB patients, total of 72 ears. Intra-person comparison was done, by dividing ears into two groups, the case group, 36 ears (LVAS with HJB); and the control group, 36 ears (LVAS without HJB). Air conduction thresholds (250Hz - 4000Hz), bone conduction thresholds (250Hz - 1000Hz), and air bone gap (250Hz - 1000Hz) were analyzed and compared between the group. Result: There were statistical significant differences in AC thresholds at 250Hz, 500Hz, 2000Hz and 4000Hz between the groups, p <0.05. But there was no statistical significant difference at 1000Hz, p>0.05. There were statistical significant differences in BC thresholds at 250Hz and 500Hz, p<0.05, but there was no statistical difference at 1000Hz. There were no significant differences in air bone gap at 250Hz, 500Hz, and 1000Hz between the two groups. Conclusion: LVAS with concurrent HJB was found to have higher air conduction thresholds, especially at 250Hz, 500Hz, 2000Hz and 4000Hz. Bone conduction thresholds were higher at 250 and 500Hz. Air bone gap at 250Hz, 500Hz and 1000Hz, were not significantly higher in LVAS with concurrent HJB.